Traduction des sigles dans le contexte audiovisuel – un dialogue réussi ? - Borowczyk, Paulina (Wydawnictwo Naukowe UAM, 2012)
In the following article, the results of our study about the translation of acronyms via Arte TV news will be presented. First, we will submit the definition of acronyms, then discuss the matter of difficulties which may appear when translating acronyms from one language into another. Finally, we will introduce the different translation procedures used by translators when they are confronted with different kinds of acronyms (names of political parties, names of associations) which we understand as terms related to sociocultural aspects. Some samples from Arte TV news will be provided as a support for this article.
Translation of acronyms in the audiovisual context – a successful dialogue?
Keywords: acronym; translation of acronyms; audiovisual context; Arte TV